Transient Tachypnea of the Newborn: The Treatment Strategies - ÖZEK, EREN (BENTHAM SCIENCE PUBL LTD, 2012)
Transient tachypnea of the newborn results from delayed clearance of lung fluid and is a common cause of admission of full term and late preterm infants to neonatal intensive care units. The condition is particularly common after elective cesarean section. Conventional treatment involves supplemental oxygen, withholding enteral feeds and administration of intravenous fluids and antibiotics. Rarely, infants require CPAP and mechanical ventilation. Occasionally some babies develop severe hypoxemia and may require high concentrations of oxygen. The most effective strategy for accelerating reabsorbtion of fetal lung fluid is exogenous glucocorticoids. Potential therapies for TTN must be based on an understanding of the physiology of normal fetal lung fluid clearence at bith. Furosemide, racemic epinephrine and inhaled - agonists have been studied for possible benefit in TTN. The routine administration of these drugs can not be recommended unless additional data become available.
Keywords: Transient tachypnea; alveolar fluid; furosemide; racemic epinephrine; salbutamol; ELECTIVE CESAREAN-SECTION; RESPIRATORY-DISTRESS; SODIUM-TRANSPORT; LUNG LIQUID; FETAL LUNG; AIRWAY EPITHELIUM; VAGINAL DELIVERY; GESTATIONAL-AGE; INFANTS; CLEARANCE